The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.bpj.2017.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Variation in Single-Cell Power-Law Rheology Spans the Ensemble Variation of Cell Population

Abstract: Changes in the cytoskeletal organization within cells can be characterized by large spatial and temporal variations in rheological properties of the cell (e.g., the complex shear modulus G). Although the ensemble variation in G of single cells has been elucidated, the detailed temporal variation of G remains unknown. In this study, we investigated how the rheological properties of individual fibroblast cells change under a spatially confined environment in which the cell translational motion is highly restrict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 58 publications
(75 reference statements)
1
30
0
Order By: Relevance
“…Previous studies have reported that the number distribution of cell mechanical properties exhibits a large variation in single cells 41 , 42 and the cell stiffness and tension are very broadly varied over a long intercellular distance in a cell monolayer 43 46 . In contrast, the embryonic cells in the vegetal hemisphere exhibited broad spatiotemporal heterogeneity occurring at the single-cell level.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that the number distribution of cell mechanical properties exhibits a large variation in single cells 41 , 42 and the cell stiffness and tension are very broadly varied over a long intercellular distance in a cell monolayer 43 46 . In contrast, the embryonic cells in the vegetal hemisphere exhibited broad spatiotemporal heterogeneity occurring at the single-cell level.…”
Section: Discussionmentioning
confidence: 99%
“…with an empirically derived model known as the structural damping (or hysteretic damping) model 33,[137][138][139][140][141][142] whose complex modulus is given by:…”
Section: Structural Damping Model a Number Of Dynamic (Oscillatory) mentioning
confidence: 99%
“…where F is the loading force, d is the indentation depth, and n is the Poisson's ratio of the cell, assumed here to be 0.5 (16,(18)(19)(20)34), which corresponds to a perfectly incompressible material (33). We estimated E from the force-indentation curve in the region of d < 0.6 mm (see Fig.…”
Section: Afm Measurementsmentioning
confidence: 99%
“…The intracellular stiffness is a fundamental cell mechanical property. Previous studies of isolated single cells adhered to a substrate revealed that the intracellular stiffness-that is, the Young's modulus, E-measured by atomic force microscopy (AFM) is mainly dominated by actin cytoskeletal structures (16)(17)(18)(19) and can change in response to the rigidity of the substrate to which the cells adhere (20,21); specifically, the intracellular stiffness increases with increasing substrate rigidity. However, little is known about how the intracellular stiffness changes in response to neighboring cells in a cell monolayer system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation